Reading the Agricultural Landscape in a River Basin: Integrating Agro-ecological and Social Perspectives - P.K. Shetty, M. Murugan; M.B. Hiremath, K.G. Sreeja*, (Recent Research in Science and Technology, 2010)
Abstract Agricultural landscape of a river basin is constituted by interlinkages between resources used and social relations, both within the basin and linking the basin to the non-basin areas. Expanding scarcities of land and water resources, and the human response to these scarcities, make it imperative to freshly examine these concepts of resource interrelationships, basin unity and stewardship concerns in an agrarian landscape of a river basin from an integrated agroecological and social perspective. The trajectories of change in agricultural resource use at the river basin is conceptualized as influenced by and carried out within multilevel networks of social relations that exchange resources and engage in reciprocal interactions within and outside the river basin. Keywords: River basin, Agricultural landscape, Resource interlinkages, Stewardship, Agro-ecology, Agricultural production networks